2020
DOI: 10.1080/0267257x.2020.1751242
|View full text |Cite
|
Sign up to set email alerts
|

Determining perceptions, attitudes and behaviour towards social network site advertising in a three-country context

Abstract: Despite the growth in social media and social network advertising (SNA), scant theoretical and empirical knowledge exists on the differences between countries, and the perceptions and attitudes towards social network advertising. The purpose of the study is to investigate the relationships between users' perceptions (personal and societal), their attitudes and their behaviour towards Facebook advertising, across three countries, as well as the moderating role of privacy and general advertising attitudes. Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 131 publications
2
20
0
2
Order By: Relevance
“…We found support for this hypothesis. This finding is consistent with Wiese & Akareem (2020) conclusions, who also found that hedonic values promote a favorable attitude towards advertising. Wang et al (2009) believe that advertisers should balance the content and make the advertisement memorable and enjoyable.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found support for this hypothesis. This finding is consistent with Wiese & Akareem (2020) conclusions, who also found that hedonic values promote a favorable attitude towards advertising. Wang et al (2009) believe that advertisers should balance the content and make the advertisement memorable and enjoyable.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 93%
“…Therefore, they suggest that marketers should not use hedonic attributes in mass marketing advertisements. Instead, they should use it in customized marketing messages (Wiese & Akareem, 2020).…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of homogeneity is prevalent these days and the concept of globalization has inspired many research scholars, however, due to the disparity exists between technologically equipped and technology deprived countries, this may not be justified to set global standards for all the countries. Due to disparity exists among different countries due to their social and cultural background, religious beliefs, viewers' response towards the advertisements can not be generalized (Wiese, Akareem, 2020). It is generally believed that advertising has the power to distort audiences' perceptions and societal values (Korgaonkar et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (e.g., Chu, Kamal & Kim, 2019;Mir, 2015;Hamouda, 2018;Wiese &Akareem, 2020) have studied the link between users' PVBand theirSNS advertising acceptance. Most of them (e.g., Wiese &Akareem, 2020) examined the association between personal beliefs and users' attitude towards SNS advertising. Scarce studies examined the association between user personal beliefs about SNS advertising and their banner ad-click response.…”
Section: Introductionmentioning
confidence: 99%